¿Es conveniente una autoridad monetaria “blanda”? (2017)
Within the framework of the so-called “inflation targeting” strategy there is a discussion about the convenience for a society as to the degree of “hardness” of a monetary authority looking to defend its inflation target, and the credibility that this authority enjoys between the private agents about it. In this paper we use a neo-Keynesian stochastic dynamic general equilibrium (DSGE) model with both rational and adaptive expectations to answer this question. Our results suggest that the social problem that can be derived from a “soft” authority is that it risks losing credibility in its effort to reach a certain inflation target. In addition, we present and use a solution of the rational expectations version of the model simple enough to allow its simulations to be performed using a spreadsheet.